Evaluation of Interleukin17and Interleukin 23 expression in patients with active and latent tuberculosis infection - Heidarnezhad, Fatemeh; Asnaashari, Amir; Rezaee, Seyed Abdolrahim; Ghezelsofla, Roghayeh; Ghazvini, Kiarash; Valizadeh, Narges; Basiri, Reza; Ziaeemehr, Aghigh; Sobhani, Somayeh; Rafatpanah, Houshang (Iranian journal of basic medical sciences, 2016)
Tuberculosis is one of the most important infectious diseases with high mortality rates worldwide, especially in developing countries. Interleukin17 (IL-17) is an important acquired immunity cytokine, which is mainly produced by CD4 TH17 cells. It can recruit neutrophils and macrophages to the infected site in the lungs. IL-23 is one of the most important inducers of IL-17. In the present study, the expressions of IL-23 and IL-17 were examined in the pathogenesis of tuberculosis. Peripheral blood mononuclear cells (PBMCs) were isolated from subjects with latent tuberculosis infection (LTB) and newly diagnosed active tuberculosis patients (ATB). PBMCs were activated with purified protein derivative (PPD) for 72 hr. Activated cells were harvested, RNA was extracted, and cDNA was synthesized. IL-17 and IL-23 mRNA expressions were evaluated by real-time PCR. The frequency of Th17 cells was examined by flowcytometry. The expressions of IL-17 and IL-23 mRNA were lower in patients than subjects with LTB ( <0.05). The frequency of IL-17 producing CD4+ T cells in patients with active TB was lower than LTB subjects ( <0.05). The results of the present study might suggest that IL-17 and IL-23 play critical roles in the immune response against TB.